AB0341 Favorable Effects of Sirukumab Treatment on Physical Function and Reductions in Morning Stiffness in Patients with Active Rheumatoid Arthritis and An Inadequate Response To Disease-Modifying Anti-Rheumatic Drugs. (15th July 2016) - Thorne, C.; Takeuchi, T.; Karpouzas, G.; McQuarrie, K.; Sheng, S.; Xu, W.; Peterson, S.; Ganguly, R.; Han, C.; Fei, K.; Hsu, B.
Abstract : Background: Improvement in physical function and morning stiffness are important goals of rheumatoid arthritis (RA) treatment. Sirukumab, a selective human anti-IL6 monoclonal antibody, has recently been evaluated in a global, Phase 3 study for the treatment of RA in patients (pts) with active disease that did not respond adequately to conventional, synthetic disease-modifying antirheumatic drugs (DMARDs). Objectives: To evaluate the effects of sirukumab treatment on physical function and morning stiffness in pts with active RA refractory to DMARDs. Methods: In this study, eligible pts with active RA and inadequate response to DMARDs were randomized (1:1:1) to treatment with sirukumab SC 50mg q4w, sirukumab SC 100mg q2w, or placebo SC q2w. In the placebo group, pts with insufficient (<20%) improvement at Wks 18 or 40 or still on placebo at Week 52 were re-randomized to receive 1 of the 2 sirukumab doses. Pts completed the HAQ-DI at baseline (BL) and 16 subsequent study visits from Week 2 to 52. A clinically meaningful improvement in HAQ-DI from BL was defined as a change (reduction) of 0.22 in HAQ-DI, 1 and a normal HAQ-DI score was defined as ≤0.5. The average duration of daily morning stiffness during the previous week in minutes (0–1440 minutes) was evaluated at the same visits as the HAQ-DI. Results: A significantly greater improvement from BL in the mean HAQ-DI score was observed for both doses of sirukumab compared with placebo at all time points from Wk 2 through to Wk 52 (all P ≤0.006; Table). Improvements from BL in the HAQ-DI score were clinically meaningful (change of −0.22) for a significantly greater proportion of pts with sirukumab (both dose regimens) compared with placebo from Wk 4 onwards (all P <0.001). At Wks 24 and 52, a significantly greater proportion of pts achieved a HAQ-DI score of ≤0.5 with both doses of sirukumab compared with placebo (all P <0.001). In addition, there was a significantly greater reduction from BL in the duration of morning stiffness with both doses of sirukumab compared with placebo at Wks 16, 24, and 52 (all P ≤0.022). Conclusions: Sirukumab treatment in pts with active RA refractory to DMARDs was associated with early, sustained, and clinically meaningful improvement in both physical function and morning stiffness, which are key treatment goals for pts with RA. References: Maska L, et al. Arthritis Care Res. 2011;63(S11):S4-S13. Disclosure of Interest: C. Thorne Grant/research support from: Abbvie, Amgen, Celgene, Lilly, Novartis, Pfizer, Sanofi, and UCB, Consultant for: Abbvie, Amgen, Celgene, Centocor, Genzyme, Hospira, Janssen, Lilly, Medexus/Medac, Merck, Novartis, Pfizer, Sanofi, and UCB, Speakers bureau: Medexus/Medac, T. Takeuchi Grant/research support from: Astellas Pharma, Bristol–Myers K.K., Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Eisai Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahikasei Pharma Corp., and Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., and Asahi Kasei Medical K.K., abbivie GK, Daiichi Sankyo Co., Ltd., Bristol–Myers K.K., Nipponkayaku Co.Ltd., Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical Co, . Ltd., Eisai Co., Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., and Takeda Pharmaceutical Co., Ltd., Astellas Pharma, and Diaichi Sankyo Co., Ltd., Celtrion, Nipponkayaku Co. Ltd, G. Karpouzas Consultant for: Janssen, Speakers bureau: Janssen, K. McQuarrie Employee of: Janssen Research & Development, LLC, S. Sheng Shareholder of: Janssen Research & Development, LLC, Employee of: Janssen Research & Development, LLC, W. Xu Employee of: Janssen Research & Development, LLC, S. Peterson Shareholder of: Janssen Research & Development, LLC, Employee of: Janssen Research & Development, LLC, R. Ganguly Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, C. Han Shareholder of: Janssen Research & Development, LLC, Employee of: Janssen Research & Development, LLC, K. Fei Shareholder of: Janssen Research & Development, LLC, Employee of: Janssen Research & Development, LLC, B. Hsu Shareholder of: Janssen Research & Development, LLC, Employee of: Janssen Research & Development, LLC